Study of co-pyrolysis kinetics, synergetic effects, and thermodynamics of coal and biomass blends. Issue 3 (14th September 2022) - Prabhakar, Ashok; Sadhukhan, Anup Kumar; Gupta, Parthapratim
ABSTRACT: The present work investigates the thermochemical conversion characteristics, reaction kinetics, and thermodynamic behavior of coal and biomass (Rice husk (RH)) blend pyrolysis in a TG reactor. Three different proportions of biomass (75, 50, and 25%) are blended with sub-bituminous Indian coal for the co-pyrolysis study. Pure coal and pure RH pyrolysis is characterized by three reaction stages, whereas the blended sample shows a four-stage thermal degradation reaction. A significant synergy is not found in the present study. Model-free techniques (FWO, KAS, and Starnik) are used to estimate the activation energy for various blending mixtures of the feed samples. The activation energy obtained for the equal mass ratio of coal and RH using the KAS, FWO, and Starnik methods is 61.45, 76.58, and 75.54 kJ/mol, respectively. The reaction order for coal: RH blend 25:75, 50:50, and 75:25 is estimated to be 4, 2.4, and 1.3, respectively. The favorable activation energy ( Eα ) is found for the blending mixture of 50% coal and 50% RH. The positive value of ΔH indicates the endothermic nature of pyrolysis. The positive and negative values of ΔS indicate the complexity and nonspontaneous nature of coal and biomass blend pyrolysis. The average Entropy ( ΔS ) for an increasing % of coal is decreasing and the value comes to negative for 75% coal, indicating that thermal equilibrium is favorable for a higher % of coal.